Relationship between university organizational management climate, teacher self-efficacy and job satisfaction in Chinese university - Jin, Ying; Che Hassan, Norlizah (Human Resource Management Academic Research Society, 2022)
Taking university teachers as the survey object and sample survey the current situation of university Teachers' organizational management climate, teachers' self-efficacy and teachers' job satisfaction, discusses the correlation and direction of action among the three, and constructs a simple structural equation model among the three. The results of structural equation model show that there is a significant positive correlation among organizational management climate, teachers' self-efficacy and teachers' job satisfaction; The organizational management climate in colleges and universities affects teachers' job satisfaction through the mediating effect of teachers' self-efficacy How to create a good organizational and management atmosphere in colleges and universities, so as to stimulate teachers' sense of self-efficacy and improve teachers' job satisfaction is undoubtedly an important work that cannot be ignored in Chinese colleges and universities